Arabic translation, cultural adaptation, and pre-testing of neighborhood environment walkability scale for adults-abbreviated (NEWS-A): Arabic NEWS-A - Al-Hazzaa, Hazzaa M.; Almarzooqi, Mezna A.; Alsukait, Reem F.; AlAhmed, Reem S.; Rakic, Severin; Cetinkaya, Volkan; Evenson, Kelly R.; Alqahtani, Saleh A. (Frontiers in Built Environment, 2024)
BackgroundImproving neighborhood walkability is critical for sustainable and livable urban development and is associated with increased physical activity. The Neighborhood Environment Walkability Scale-Abbreviated (NEWS-A) is a tool for assessing neighborhood walkability among adults. Currently, no Arabic version is available for this important walkability scale.ObjectiveTo translate the NEWS-A to Arabic, culturally adapt, and pre-test it for adults.MethodsThe NEWS-A was translated and culturally adapted using Cross-cultural Survey Guidelines and then pre-tested using 65 households selected randomly from the neighborhoods of three districts in Riyadh. After answering the survey, 55 participants took part in a semi-structured cognitive interview, which sought their understanding of the words in the Arabic questionnaire, the clarity of each item, and their suggestions for improvement.ResultsTranslation and adaptation of NEWS-A to Arabic resulted in adding two items (mosque and healthcare center) to section B of the scale (stores, facilities, and other things in your neighborhood) and one related item to section C (access to services). The total individual items became 57 instead of the original 54 items in the English version. Also, we added “ATM machine” to item 14 (Bank/credit union) in section B. In addition, the overall results of the cognitive interview showed that most of the participants understood the intended meaning of the questionnaire (99.5%). Further, 99.8% of the respondents stated that the items were not difficult to comprehend, while 100% of the sample indicated that the sentences were comfortable and not sensitive to them.ConclusionTranslating, adapting, and pre-testing the NEWS-A resulted in retaining all the original items and adding three additional items. The Arabic NEWS-A provides an important tool for future research on neighborhood environment walkability among adults.